Essential Amino Acids and Exercise Tolerance in Elderly Muscle-Depleted Subjects with Chronic Diseases : A Rehabilitation without Rehabilitation? - Aquilani, Roberto; D’Antona, Giuseppe; Baiardi, Paola; Gambino, Arianna; Iadarola, Paolo; Viglio, Simona; Pasini, Evasio; Verri, Manuela; Barbieri, Annalisa; Boschi, Federica (BioMed research international, 2014)
Exercise intolerance remains problematic in subjects with chronic heart failure (CHF) and/or chronic obstructive pulmonary disease (COPD). Recent studies show that supplemented essential amino acids (EAAs) may exert beneficial effects on CHF/COPD physical capacity. The results from 3 investigations (2 conducted on CHF and 1 on COPD subjects) served as the basis for this paper. The 3 studies consistently showed that elderly CHF and COPD improved exercise intolerance after 1–3 months of EAA supplementation (8 g/d). In CHF exercise capacity increased 18.7% to 23% (watts; bicycle test), and 12% to 22% (meters) in 6 min walking test. Moreover, patients reduced their resting plasma lactate levels (by 25%) and improved tissue insulin sensitivity by 16% (HOMA index). COPD subjects enjoyed similar benefits as CHF ones. They increased physical autonomy by 78.6% steps/day and decreased resting plasma lactate concentrations by 23%. EAA mechanisms explaining improved exercise intolerance could be increases in muscle aerobic metabolism, mass and function, and improvement of tissue insulin sensitivity (the latter only for the CHF population). These mechanisms could be accounted for by EAA’s intrinsic physiological activity which increases myofibrils and mitochondria genesis in skeletal muscle and myocardium and glucose control. Supplemented EAAs can improve the physical autonomy of subjects with CHF/COPD.